Cut-off points for height, weight and body mass index adjusted bioimpedance analysis measurements of muscle mass with use of different threshold definitions. (9th April 2021) - Bahat, Gulistan; Tufan, Asli; Kilic, Cihan; Aydın, Tugba; Akpinar, Timur Selçuk; Kose, Murat; Erten, Nilgun; Karan, Mehmet Akif; Cruz-Jentoft, Alfonso J.
Abstract: Aim: Low muscle mass (LMM) is a prerequisite to define sarcopenia. We aimed to report muscle-mass reference cut-off points adjusted for height and weight as muscle-mass threshold best discriminating muscle-weakness and adjusted for body mass index (BMI) significantly lower than that of healthy young population. Material and method: We included young adults between 18 and 39 years and community dwelling older adults 60–99 years of age. Bioimpedance analysis (BIA) was used to assess skeletal muscle mass. Skeletal muscle mass index (SMMI) adjusted for height, weight, BMI were calculated [SMMI (height), SMMI (weight), SMMI (BMI)]. Handgrip strength was evaluated with Jamar hydraulic dynamometer for muscle-strength. SMMI (height) and SMMI (weight) cut-offs that predict low muscle-strength were calculated with receiver operator characteristic (ROC) analysis. Low muscle-strength was evaluated by three different thresholds, i.e. 32 kg/22 kg, 30 kg/20 kg, 26 kg/16 kg in males/females. SMMI (BMI) cut-offs were calculated as "mean young SMMI (BMI)–two standard deviation." Results: The young and older reference groups included 301 and 992 individuals, respectively. LMM cut-points for SMMI (height) were (i) 10.8 vs. 8.9 kg/m 2 for 32/22 kg; 10.8 vs. 9.4 kg/m 2 for 30/20 kg and 11.1 vs. 8.9 kg/m 2 for the 26/16 kg thresholds, in males and females, respectively. LMM cut-points for the SMMI (weight) were 40.6% and 33.2% for the all three studied muscle-strength thresholds for males and females, respectively. For all the analyses sensitivity, specificity and likelihood ratios were not sufficiently high in both genders. The SMMI (BMI) cut-points were 1.049 vs. 0.823 kg/BMI for males and females, respectively. Conclusions: We presented the very first cut-off thresholds for muscle-mass adjusted by height and weight that best discriminate muscle-weakness in the older adults and by BMI that is significantly lower than that of healthy young population. This study suggests that correlation between total skeletal muscle mass measured by BIA (either adjusted for height or weight) and muscle strength is low.